Stabilizing the Edge: Southeastern and Mid-Atlantic Shorescapes Facing Sea-level Rise - Jones, Shana; Pippin, Scott (Columbia Journal of Environmental Law, 2021)
Ecologically fragile coasts face increasing pressures from economic development, population growth, hurricanes, extreme weather events, and sea-level rise. This Article addresses the last of these threats, focusing on shoreline stabilization law and policy. “Living shorelines” and similar nature-based approaches are often better alternatives to stabilize shorelines and reduce dangerous erosion than traditional hard “armoring” practices such as bulkheads and seawalls. Shoreline armoring is also closely associated with habitat loss in intertidal and subtidal areas, affecting fisheries’ production, water quality, and other valuable ecosystem services. Adapting shoreline stabilization infrastructure and approaches to sea-level rise will require measures that improve federal, state, and local governance mechanisms; promote nature-based management practices; and change property owner behavior that affects coastal areas. This Article analyzes ocean-facing and estuarine protection laws in the Southeast and Mid-Atlantic states to identify how governance mechanisms could better integrate sea-level rise into coastal management practices and decision-making, concentrating in particular on policies designed to reduce erosion and flooding. Our research revealed important distinctions between how we manage ocean-facing and estuarine-facing shorelines, as well as a wide variety of values and interests driving these differences. A regulatory system more strongly connected by science to the applicable natural systems is possible and desirable. To our knowledge, no such comprehensive overview or comparison of these shorescape protection, setback, and stabilization laws currently exists. Ultimately, the Article fills an important research gap in the existing climate change and coastal management literature, as it sets the stage for incorporating interdisciplinary findings from coastal science and social science research with legal and policy mechanisms to inform coastal zone management.